APLIKASI INFO UNIT TRANSFUSI DARAH PMI KABUPATEN PROBOLINGGO BERBASIS ANDROID - Novia Rizqiana; Sulistiyanto Sulistiyanto; Syaiful Huda (SENTIA 2016, 2016)
Information about the benefits and requirements of blood donors, the amount of blood stock available, donor back schedule to donors and information activities a donor event is one of the function’s administration activities which done by UTD PMI Probolinggo Regency. However, this cannot be channeled to the public. so that people lacked knowledge about the information regarding blood donation. See these problems, the researcher builts application information UTD PMI Probolinggo Regency android-based to simplify the admin to manage data regarding blood donation and publish it to the public.The result of this research is the construction of an application the information UTD PMI Probolinggo Regency which can help UTD PMI about blood donor information to public. So that people can get that information. This application can help and interest to people for blood donor because this information and blood donor rule and information about blood donor activity.